ANALISIS STRATEGI DIFERENSIASI (Kasus Produk Telkom Speedy di Plasa Telkom Pekanbaru) - Azwar, M.; Othman, Lie (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research took place in The Plasa Telkom Pekanbaru. This research based on the amount of market opportunities to telecommunications services (internet) in Riau. These conditions provide an opportunity and also threat to telecommunications service provider (internet) business that targeting the same market, that effected competition conditions being increased intensely. These condition forced The Plasa Telkom Pekanbaru to designing and implementing an appropriate and efficient differentiation strategy to attract and retain customers. This study aims to analyze the differentiation strategy implemented of The Plasa Telkom Pekanbaru and constraints experienced in the face of telecommunications services in Riau.The Author used descriptive quantitative analysis method, Used questionnaire and interview to collecting data, and used accidental sampling as sample. Source of data was used primary data or obtained directly from the object of research data, and secondary data is data which Author collected from The Plasa Telkom Pekanbaru.The results of this research indicate that the differentiation strategy that has been implemented by The Plasa Telkom Pekanbaru is appropriate, but the strategy style of Speedy’s product must be considered and improved.Keywords: Differentiation strategy, telecommunication services, Telkom’s products